Correlation between Lifestyle Factors and Blood Glucose Levels to Elderly at Elderly Posyandu in Pelem Village, Kediri District - Erni Rahmawati; Dwi Rahayu; Pratiwi Yuliansari; Fresty Africia (LP3M Universitas Muhammadiyah Tasikmalaya, 2024)
Data from the International Diabetes Federation (IDF) in 2017, the global prevalence rate was 425 million people in the world experiencing DM. Estimated in 2045, it will increase to 48% (629 million) among DM sufferers aged 20-79 years. Elderly is a process of aging with increasing age, which is characterized by decreasing the function of the body's organs. To determine the correlation between lifestyle factors and blood glucose levels to elderly at Elderly Posyandu in Pelem Village, Kediri District. The research design was quantitative research with a cross-sectional approach. The research sample was elderly from Pelem Village, totaling 65 respondents. The independent variables were lifestyle factors (physical activity, frequency of carbohydrate consumption, frequency of fiber consumption, obesity and medication compliance), while the dependent variable was blood glucose level. The measuring instruments used questionnaires and GDA measurement tools. Data processing used univariate and bivariate tests with chi-square. Univariate analysis showed that most of elderly were aged 66-70 years (38.5%), male (63.1%), low education (52.3%) and not working (41.5%). Bivariate results showed correlation between lifestyle factors such as physical activity (p=0.007), frequency of carbohydrate consumption (p=0.028), frequency of fiber consumption (p=0.005), obesity (p=0.029) and medication compliance (p=0.032) and blood glucose levels to elderly. There was correlation between lifestyle factors and blood glucose levels to elderly.